Spatio-temporal characteristics and determinants of anthropogenic nitrogen and phosphorus inputs in an ecologically fragile karst basin: Environmental responses and management strategies. (December 2021) - Xu, Guoyu; Xiao, Jie; Oliver, David M.; Yang, Zhiqi; Xiong, Kangning; Zhao, Zhongming; Zheng, Lilin; Fan, Hongxiang; Zhang, Fuxiang
Graphical abstract: Highlights: Wujiang River Basin (WRB) has high spatial heterogeneity in anthropogenic nitrogen (N) and phosphorus (P) inputs. Grid fractal dimension and Geographical Detector Model are used to explore environmental responses and determinants to NANI and NAPI. Decoupling between crop production and livestock feed has increased inputs of NANI and NAPI. Agricultural vs ecosystem trade-offs will represent important potential N and P sources. Abstract: Excessive nitrogen and phosphorus inputs to land and subsequent export to water via runoff leads to aquatic ecosystem deterioration. The WRB is the world's largest karst basin which is characterized by a fragile ecosystem coupling with high population pressure, and the transformation of intensive agriculture. Quantifying different sources of pollution in karst regions is challenging due to the complexity of landscape topography and geology coupled with high transmissivity and connectivity of subsurface hydrological systems. This results in large uncertainty associated with nitrogen (N) and phosphorus (P) flow pathways. This combination of factors contributes to the WRB being a high priority for quantitatively understanding the contribution of regional nutrient inputs and those of other major water quality determinants. Here we applied the latest statistical data (2000–2018) and simple quasi-mass-balance methods of net anthropogenic nitrogen and phosphorus inputs (NANI and NAPI) to estimate spatio-temporal heterogeneity of N and P inputs. The results show that while NANI and NAPI are first decreasing, this is followed by an increasing trend during 2000–2018, with average values of 11262.06 ± 2732 kg N km − 2  yr −1 and 2653.91 ± 863 kg P km −2  yr −1 respectively. High N and P concentrations in the river drainage network are related to the spatial distribution of excessive inputs of N and P. Rapid urbanization, livestock farming and the conflicts between economic development and lagged-environmental management are the main reasons for the incremental regional N and P inputs. Management decisions on nutrient pollution in karst regions need careful consideration to reduce ecological impacts and contamination of karst aquifers. This study provides new insight for policy and decision making in the WRB, highlighting policy options for managing nutrient inputs and providing recommendations for closing the science-policy divide.